The presence of God in the Kantian conception of Gewissen - Placencia, Luis (Con-Textos Kantianos. International Journal of Philosophy, 2024)
his article addresses - starting from the question of Kant's relation to "atheism" - the question of the presence of the notion of "God" in his practical philosophy, more specifically still in his conception of "moral conscience" (Gewissen). Attention will be paid primarily to the role played by this notion in the well-known metaphor of the "tribunal" with which Kant attempts to present some salient features of his conception of Gewissen.